Finding it : and satisfying my hunger for life without opening the fridge - Bertinelli, Valerie, 1960- (New York : Free Press, 2009)
A former TV star and author of the #1 best seller Losing It returns with an intimate account of the challenges she faced after reaching her goal weight--including her son falling in love, her mother's health issues, her anger over her father's conservative politics, her struggles with faith, and more.
Keywords: Bertinelli, Valerie, -- 1960-; Television actors and actresses -- United States -- Biography